Perilipin-related protein regulates lipid metabolism in C. elegans - Chughtai,Ahmed A.; Kaššák,Filip; Kostrouchová,Markéta; Novotný,Jan Philipp; Krause,Michael W.; Saudek,Vladimír; Kostrouch,Zdenek; Kostrouchová,Marta (PeerJ PrePrints, 2015)
The perilipins are lipid droplet surface proteins that contribute to fat metabolism by controlling the access of lipids to lipolytic enzymes. Perilipins have been identified in organisms as diverse as metazoa, fungi, and amoebas but strikingly not in nematodes. Here we identify the protein encoded by the W01A8.1 gene in Caenorhabditis elegans as the closest homologue of metazoan perilipin. We demonstrate that nematode W01A8.1 is a cytoplasmic protein residing on lipid droplets. Human perilipins 1 and 2 localize in transgenic C. elegans on the same structures as proteins expressed from W01A8.1 gene. Inhibition and elimination of W01A8.1 affects the appearance of lipid droplets especially visible as the formation of large lipid droplets localized around the dividing nucleus during the early zygotic divisions. This phenomenon disappears in later stages of embryogenesis indicating the existence of an additional mechanism of lipid regulation in C. elegans. Our results demonstrate that perilipin-related regulation of fat metabolism is conserved in nematodes and provide new possibilities for functional studies of lipid metabolism.
Keywords: perilipin; perilipin-related protein in C. elegans; Caenorhabditis elegans; lipid droplets; fat metabolism